Kinds of Food and Drinks in Morocco in the Period of Al-Murabteen and Al-Moahideen (Journal of the College of Education for Women, 2019)
Cooking was of great importance in the Islamic Arabic culture and thepeople of Morocco have shown great interest in this aspect and also in thevariety in the making of food. They used all kinds of meat of and have showninterest in preserving and distributing it .The people of Morocco used theadditives in their cooking such as salt, saffron and many other kinds to addspecial flavor and taste and their cooking a distinctive flavor.Sweet and pastry, in addition to the drinks, represented another aspect of theMoroccan kitchen. At that time women were brought as slaves from Sudanand as a result they brought their experience in the making of sweets andpastry with them to Morocco, they used sugar, fat, wheat in addition todifferent kinds of nuts.In order to keep the high standard of food there was a quality controlover food at that time and the owner of the market place was in charge of thequality of food, the cooking place and its cleanliness and they were also incharge of punishing the swindlers.